Implication of PI3K/Akt pathway in pancreatic cancer: When PI3K isoforms matter?. (September 2015) - Baer, Romain; Cintas, Célia; Therville, Nicole; Guillermet-Guibert, Julie
Abstract: Pancreatic cancer belongs to the incurable family of solid cancers. Despite of a recent better understanding its molecular biology, and an increased number of clinical trials, there is still a lack for innovative targeted therapies to fight this deadly malignancy. PI3K/Akt signalling is one of the most commonly deregulated signalling pathways in cancer, which explains the massive attention from many pharmaceutical companies over the ten past years on these signalling molecules. The already developed small molecule inhibitors are currently under clinical trial in various cancer types. Class I PI3Ks have 4 isoforms for which the role in physiology starts to be well described in the literature. Data are more unclear for their differential involvement in oncogenesis. In this review, we will discuss about the cognitive and therapeutic potential of targeting this signalling pathway and in particular Class I PI3K isoforms for pancreatic cancer treatment. Isoform-specificity of PI3K inhibitors are currently designed to achieve the same goal as pan-PI3K inhibitors but without potential adverse effects. We will discuss if such strategy is relevant in pancreatic adenocarcinoma.